2012
DOI: 10.1021/nn204762w
|View full text |Cite
|
Sign up to set email alerts
|

Self-Propelled Nanotools

Abstract: We describe nanoscale tools in the form of autonomous and remotely guided catalytically self-propelled InGaAs/GaAs/(Cr)Pt tubes. These rolled-up tubes with diameters in the range of 280-600 nm move in hydrogen peroxide solutions with speeds as high as 180 μm s(-1). The effective transfer of chemical energy to translational motion has allowed these tubes to perform useful tasks such as transport of cargo. Furthermore, we observed that, while cylindrically rolled-up tubes move in a straight line, asymmetrically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
321
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(326 citation statements)
references
References 52 publications
2
321
0
3
Order By: Relevance
“…For example, Sanchez et al reported the use of self-propelled rolled-up microtubes to drill and embed themselves into biomaterials such as cells which can be potentially used to address the endosome escape challenge and deliver the drug or gene inside the cell. 50 Another study by Wu et al 51 demonstrated that by taking advantages of photothermal effects, PtNP-modied polyelectrolyte multilayer microtube engines can be used for targeted recognition and subsequent killing of cancer cells.…”
Section: 38mentioning
confidence: 99%
“…For example, Sanchez et al reported the use of self-propelled rolled-up microtubes to drill and embed themselves into biomaterials such as cells which can be potentially used to address the endosome escape challenge and deliver the drug or gene inside the cell. 50 Another study by Wu et al 51 demonstrated that by taking advantages of photothermal effects, PtNP-modied polyelectrolyte multilayer microtube engines can be used for targeted recognition and subsequent killing of cancer cells.…”
Section: 38mentioning
confidence: 99%
“…[1][2] They self-propel by harvesting chemical energies from fuels in suspension, such as hydrogen peroxide. [18][19] Recently, substantial research efforts have been focused on strategically designing and fabricating catalytic nanomotors with an array of compositions and geometries, such as bimetallic nanorods, [18][19][20] catalytic microtubes, [21][22][23] and Janus particles [24][25][26][27] . The efforts lead towards dramatic improvement of propulsion speeds up to hundreds of μm/sec (or 100 body lengths per second), [19][20][21] and readiness in harnessing energy from a variety of fuels, such as hydrazine, 28 urea [29][30] and even pure water 13,26 .…”
Section: Introductionmentioning
confidence: 99%
“…One is to apply an external field as the driving force, 7,8 which is limited by the specific properties of the materials and is strongly dependent on manual control. The other solution is to introduce an external material flow to provide chemical power, such as the decomposition of hydrogen peroxide 4,[9][10][11][12][13][14][15][16][17][18][19] or the reduction of protons by zinc 20,21 for bubble propulsion or other propelling mechanisms, the Marangoni effect caused by a surface tension gradient [22][23][24] or biomotors such as myosins, kinesins and dyneins via the hydrolysis of adenosine triphosphate. 25 As a branch of material flow research, the Marangoni effect is a facile, environmentally benign and rapidly responsive method for driving small objects automatically.…”
Section: Introductionmentioning
confidence: 99%